2014
DOI: 10.1128/iai.01152-13
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to Acute Rheumatic Fever Based on Differential Expression of Genes Involved in Cytotoxicity, Chemotaxis, and Apoptosis

Abstract: It is unknown why only some individuals are susceptible to acute rheumatic fever (ARF). We investigated whether there are differences in the immune response, detectable by gene expression, between individuals who are susceptible to ARF and those who are not. Peripheral blood mononuclear cells (PBMCs) from 15 ARF-susceptible and 10 nonsusceptible (control) adults were stimulated with rheumatogenic (Rh؉) group A streptococci (GAS) or nonrheumatogenic (Rh؊) GAS. RNA from stimulated PBMCs from each subject was coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Heart valve-derived T cells that recognise myosin peptides produce IFNγ, in addition to TNF and IL-10 [187]. However, transcriptional profiling of PBMC in RHD patients showed that IFNγ was not as strongly induced by rheumatogenic GAS when compared with non-RHD controls, suggesting blunted Th1 polarisation [276]. Indeed, Th2 polarisation may actually protect the heart from cumulative damage in RHD.…”
Section: Cytokines In Arf and Rhdmentioning
confidence: 99%
“…Heart valve-derived T cells that recognise myosin peptides produce IFNγ, in addition to TNF and IL-10 [187]. However, transcriptional profiling of PBMC in RHD patients showed that IFNγ was not as strongly induced by rheumatogenic GAS when compared with non-RHD controls, suggesting blunted Th1 polarisation [276]. Indeed, Th2 polarisation may actually protect the heart from cumulative damage in RHD.…”
Section: Cytokines In Arf and Rhdmentioning
confidence: 99%
“…Thirteen genes were thought to be involved, and as seven of these genes were involved with the immune system, it strongly suggested defective or a failed immune response may contribute to the development of ARF in susceptible individuals [22]. There is not yet a single panel of genetic polymorphisms that have been clearly shown to be associated with ARF, with ongoing research needed.…”
Section: Investigative Toolsmentioning
confidence: 97%
“…Lynskey et al [33] have now identified that natural truncation of protein RocA causes this hyperencapsulation and the associated characteristics of carriage longevity and transmissibility. Studies of cytokine responses and monocyte expression provide clues to the aberrant host responses occurring in ARF [34][35][36], including elevated levels of tumour necrosis factor (TNF) a and interleukin-8 [37]. Findings regarding interleukin-10 are inconsistent [35,36,38].…”
Section: Pathogenesis Of Acute Rheumatic Fevermentioning
confidence: 99%